1997
DOI: 10.1128/aem.63.4.1588-1593.1997
|View full text |Cite
|
Sign up to set email alerts
|

On-farm monitoring of mouse-invasive Salmonella enterica serovar enteritidis and a model for its association with the production of contaminated eggs

Abstract: Mice (Mus musculus) captured in henhouses were assessed for the presence of salmonellae in spleens. Of 621 and 526 spleens cultured during the first and second years of collection, 25.0 and 17.9%, respectively, were positive for Salmonella enterica serovar Enteritidis. Contaminated eggs were cultured from nine houses during the first year of sampling, and for eight of these houses, serovar Enteritidis was recovered from the spleens of mice. Rank sum statistical analysis of positive mouse spleens indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2001
2001
2009
2009

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(40 citation statements)
references
References 17 publications
0
37
0
1
Order By: Relevance
“…Although Salmonella is commonly transmitted to humans from poultry and pigs, house mice are often claimed to be the initial reservoir (Hart et al 1997), and Davies and Wray (1995) have reported Salmonella in 48á7% of house mice from poultry units. However, comparisons by Henzler and Opitz (1992) and Guard-Petter et al (1997) show that the prevalence tends to be lower in units with no history of Salmonella in poultry (6á0% and 0á4% in the two studies, respectively) compared with those with recent Salmonella infections (31á8% and 31á5%). This suggests that although house mice may have been the initial source of pathogenic Salmonella in poultry¯ocks (Ba Èumler et al 2000), it is probably now infected livestock (especially poultry) that are infecting the mice, which then serve as a reservoir for re-infection (Henzler and Opitz 1992;Davies and Wray 1995).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Although Salmonella is commonly transmitted to humans from poultry and pigs, house mice are often claimed to be the initial reservoir (Hart et al 1997), and Davies and Wray (1995) have reported Salmonella in 48á7% of house mice from poultry units. However, comparisons by Henzler and Opitz (1992) and Guard-Petter et al (1997) show that the prevalence tends to be lower in units with no history of Salmonella in poultry (6á0% and 0á4% in the two studies, respectively) compared with those with recent Salmonella infections (31á8% and 31á5%). This suggests that although house mice may have been the initial source of pathogenic Salmonella in poultry¯ocks (Ba Èumler et al 2000), it is probably now infected livestock (especially poultry) that are infecting the mice, which then serve as a reservoir for re-infection (Henzler and Opitz 1992;Davies and Wray 1995).…”
Section: Introductionmentioning
confidence: 83%
“…There was a high rate of turnover in the house mouse population (only 21% of individuals were recaught from one month to the next), making long-term persistence of infections less likely. However, some Salmonella strains have been found to persist within commensal rodent populations for months or even years (Sato et al 1970 1 ;Henzler and Opitz 1992;Guard-Petter et al 1997). Due to the high population turnover, few mice were tested on more than one occasion, so no conclusions can be drawn about the pattern of infection in an individual.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are three major theories concerning the origin of Salmonella illness associated with egg contamination. First, clonal expansion of an unusual strain, which results in more contaminated eggs in the marketplace owing to an enhanced ability of the organism to be invasive in chickens or otherwise to reach and survive within the internal contents of eggs (Petter, 1993;Guard-Petter et al, 1997;Guard-Petter, 1998) may be a factor; secondly, waning flock immunity to Salmonella enterica serovar Pullorum, an avian-adapted salmonellae that also contaminates eggs internally, might have provided an ecological niche for the expansion of S. Enteritidis (Rabsch et al, 2000); thirdly, Salmonella infections in rodents may have been the cause of a change in infection dynamics, resulting in the emergence of S. Enteritidis in flocks kept in houses that have resident infected mice (Henzler and Opitz, 1992;Henzler et al, 1998). The first theory suggests that it should be possible to identify biological markers unique to egg-contaminating S. Enteritidis, whereas the last two theories argue that host factors are of primary importance.…”
Section: Introductionmentioning
confidence: 99%
“…Mice are important in the epidemiology of Salmonella on farms as not only do they act as potential long-term carriers of the organism but also they may amplify numbers of organisms in the environment, deposit highly contaminated faeces directly into feeders. Passage of S. Enteritidis in mice may also selectively amplify more virulent and egg invasive strains (Humphrey et al ., 1996;Guard-Petter et al ., 1997;Henzler et al ., 1998;Guard-Petter, 2001). Carriage of Salmonella by arthropods has also been reported previously (Graffar and Mertens, 1950;Fischer, 1999;Olsen and Hammack, 2000) but the seasonal appearance of contaminated ground beetles and their larvae in one of the empty poultry houses during two consecutive summers was unexpected.…”
Section: Discussionmentioning
confidence: 99%